Memories of the Ashaninka of the Ene River during the Peruvian internal war - Balaguer, Alejandro (2024)
In 1990 I was a young photojournalist and foreign press correspondent in Peru. After having traveled through several war zones in Ayacucho, I ventured into the remote Ene River valley, where a great drama was unfolding. As the army advanced and the Shining Path retreated into the bush, hundreds of Ashaninka were being recovered and were arriving as refugees in the Ashaninka community of Cutivireni after having been kidnapped and taken captive by the armed columns of Shining Pathists. There are thousands of photographs and memories of those terrible days in the community that I want to share.Memories of human beings barricaded to survive; without food, refugees, destitute against disease, with cholera raging, taking rifle fire, avoiding murderous mines, sharing fears and smiles, and death ever-present. Recurring images that keep coming back to me and remain vivid despite the years, in memory and on photographic paper, and which I now try to awaken from oblivion.